Observing once‐in‐a‐lifetime weather: the early snows of October 2008. (10th April 2020) - Currie, Ian
Abstract : Snow lying in October at low levels in the UK is unusual even in Scotland, which is closer to the source of Arctic air necessary for its occurrence and with lower sea temperatures. Rarity increases further south, and for the southern Home Counties a single occurrence of lying snow was not reported in October during the twentieth century. As a consequence, the snow which fell in Surrey during the evening and into the night on 28 October 2008, establishing a snow cover, was the first such occasion in over 120 years. In places, snow lay for two days, during a period in which the month of October has shown significant warming. I have been recording the weather instrumentally for nigh on 58 years. From 1979 until 2018 my observations were from Coulsdon (128m amsl) on the Surrey‐south London border, just south of Croydon. During this time I experienced some outstanding meteorological events, including the Great October storm of 1987. But there was one occurrence that has proved unique, namely the early snowfall of 28‐29 October 2008, which affected even central London. It took many observers by surprise though it was forecast but not quite so far south and was somewhat underreported by the media. Abstract : Scenes more reminiscent of January were witnessed across parts of southern England during the evening of 28 October 2008 as seen here at Banstead, Surrey. How rare is a lying snowfall in this mid autumn month south of the Thames? © Mark Davison by permission.)